Evaluation of Lactococcus lactis carrying active For t 2 protein in immunotherapy for Forcipomyia taiwana allergy in mice - Mey-Fann Lee, PhD; Yi-Hsing Chen, MD, PhD; Chu-Hui Chiang, PhD; Chi-Sheng Wu, MS; Nancy M. Wang, PhD (World Allergy Organization Journal, 2025)
Background: Forcipomyia taiwana (Diptera: Ceratopogonidae) allergy is Taiwan's most prevalent biting insect allergy. Our previous studies identified and cloned major F. taiwana allergens For t 2 and determined its strong immunogenicity to human fibroblasts. This study investigated whether oral administration of food-grade Lactococcus lactis containing For t 2 ameliorated midge-allergic symptoms in a mouse model. Methods: BALB/c mice, divided into viable, sonicated, and autoclaved groups, were fed with L. lactis-For t 2 5 times weekly for 4 weeks. Immune molecules related to allergies in serum were analyzed and 16S rRNA profiles of fecal samples were compared. Results: The results revealed administration of L. lactis-For t 2 significantly decreased the level of total IgE and ameliorated midge allergen-challenge-induced scratch bouts found in the viable and sonicated groups, but not the autoclaved group. The sonicated group showed a significant reduction in IL-4, IL-13, IL-17, MCP-1, and TNF-α levels. Its effect was comparable to that of the viable group and was even more pronounced in reducing IL-9 expression. Further, we performed a comprehensive analysis of 16S rRNA profiles corresponding to fecal samples. Clostridiaceae and Clostridium were the dominant family and genus in the autoclaved group, whereas Duncaniella and Kineothrix were the dominant genus in the sonicated and viable groups, respectively. Conclusions: The results imply that mucosal allergen-specific immunotherapy of L. lactis For t 2 is a better cost-effective alternative to conventional subcutaneous allergen-specific immunotherapy. This study shows that non-viable L. lactis-derived For t 2 active protein may be a promising therapeutic for treating midge allergy.